The sincerest form of flattery: large-scale analysis of code re-use in Atari 2600 games - Aycock, John; Ganesh, Shankar; Biittner, Katie; Newell, Paul Allen; Therrien, Carl (My University, 2022)
The Atari 2600 was a prominent early video game console that had broad cultural impact, and possessed an extensive catalog of games that undoubtedly helped shape the fledgling game industry. How were these games created? We examine one development practice, code re-use, across a large-scale corpus of 1,984 ROM images using an analysis system we have developed. Our system allows us to study code re-use at whole-corpus granularity in addition to finer grained views of individual developers and companies. We combine this corpus analysis with a case study: one of the co-authors was a third-party developer for Atari 2600 games in the early 1980s, providing insight into why code re-use could occur through both oral history and artifacts preserved for over forty years. Finally, we frame our results about this development practice with an interdisciplinary, bigger-picture archaeological view of humans and technology.
Keywords: Atari 2600; game development; binary reverse engineering; archaeogaming; empirical study